2022
DOI: 10.1038/s41598-021-04269-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulated anti-VEGF therapy under the influence of lipid metabolizing proteins in Age related macular degeneration: a pilot study

Abstract: Age-related macular degeneration (AMD) is a devastating retinal disease that results in irreversible vision loss in the aged population. The complex genetic nature and degree of genetic penetrance require a redefinition of the current therapeutic strategy for AMD. We aimed to investigate the role of modifiers for current anti-VEGF therapy especially for non-responder AMD patients. We recruited 78 wet AMD cases (out of 278 AMD patients) with their socio-demographic and treatment regimen. Serum protein levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The rare LIPC rs13095226 and rs3748391 variants have also been associated with a slightly increased AMD risk [ 47 ]. Finally, LIPC variants may be associated with a poorer response to anti-VEGF therapy [ 239 ].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…The rare LIPC rs13095226 and rs3748391 variants have also been associated with a slightly increased AMD risk [ 47 ]. Finally, LIPC variants may be associated with a poorer response to anti-VEGF therapy [ 239 ].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“… 15 We have also identified that genetic variants and subsequent protein alterations especially lipid metabolising proteins (APOE and LIPC) can modulate the anti-VEGF response in wet AMD patients. 53 But, the translation of such studies to diagnostic and therapeutic advancement remains neglected because most of the studies lack the approach to consider the clinical findings, genotype, protein expression and socio-demographic variables as an integral entity to dissect the AMD complexity. Hence, we have conducted a pilot study where an association between genotype, phenotype, protein levels and demographic variables has been investigated and attempted to investigate the association of genetic differences with OCT findings of AMD patients.…”
Section: Introductionmentioning
confidence: 99%